Suspected Hepatically Localized Granulomatosis with Polyangiitis - Yamamoto, Toshiki (Intern Med, 2018)
The patient was a 72-year-old woman whose alkaline phosphatase levels had been elevated since she was 56 years old. Liver biopsies obtained when the patient was 64 and 66 years of age led to a suspicion of cholangitis caused by vasculitis. Furthermore, proteinase-3 anti-neutrophil cytoplasmic antibody positivity led to a suspicion of granulomatosis with polyangiitis, but subjective symptoms and disorders in other organs were absent, so this suspicion was not confirmed. Cholangitis caused by vasculitis rarely occurs without vasculitis in other organs. We herein report this case in which we obtained distinctive laparoscopic and imaging findings that raised suspicions of liver circulatory failure.